Políticas de tecnologia na educação e a formação de professores: um estudo da experiência do Nied/Semec-Belém-Pará - FREITAS JUNIOR, José Maria de (Universidade Federal do Pará, 2017)
This is a study about educational technology policies and teacher training from of the experience of NIED/SEMEC-Belem-PA, considering that public policies of technology in education indicate actions that, in recent years in Brazil, have not materialized in society yet, especially in public schools, as well as the teachers’ training to work with the technologies proposed by these policies. This study aims to analyze the frameworks that guide NIED/ Belem in their formative action in educational computing classroom teachers, and understand if, in fact, this action is effective under the TIC policy orientations in education. The study, from a qualitative approach, involved field research, made by semi-structured interviews, with open and closed questions, with teachers involved with NIED/Belem. The results show that teacher training in educational computing held by NIED/Belem has several limitations related to the lack of monitoring and counselling by trainers; the approach to schools; the high number of training programs that the Center coordinates; the lack of Internet access in schools; and the small number of computers in the computer labs of schools. We understand that the public policies in educational informatics, listed by MEC, have been useful as a guide for the teacher training processes, especially in the area of technology in education, so that the training of teachers in that area needs to be better treated and effective in the investigated institution.